New comprehensive metrics and nontrivial steps to formulas multi-valued logic in the automatic clustering of logical formulas Knowledge Base. II - Vikent’ev, A.A.; Avilov, M.S. (Bulletin of the Karaganda University. Mathematics Series, 2016)
This article describes the following tasks: Summarized previously entered distances and non - triviality of the measures on the n - digit case of any logic, removing restrictions on the parameters; With the new range, developed algorithms for clustering sets of formulas in the n - valued logic; Conducted clustering subsets of formulas from different knowledge bases and provides methods of comparison adapted results of various clustering algorithms.